ANOMALOUS SEISMO-ACOUSTIC WAVE PROPAGATION AND DETERMINATION SOURCE OF INFRASOUND - Ch, Bayarsaikhan; L, Tungalag; Ch, Lkhagvajav; Pichon, Alexis Le (Proceedings of the Mongolian Academy of Sciences, 2017)
The network of infrasound stations (I34MN) in Mongolia daily registers set of infrasound from various sources besides explosions. The data from explosions in mines in region and from other sources detected since 2000 to 2009 in seismic and infrasound stations is analyzed. The analysis these signals dependence of speed distribution of sound from seasonal, wind forces and direction moreover on short distances. From detected in infrasound stations (I34MN) in year 80-90 % of signals make microbaroms, the wide range of their sources is visible from the frequency analysis. From the general analysis registered seismo and acoustic signals of explosions on the seismic and infrasound networks stations miscalculate not only speeds of distribution of sounds on close distances (50-500 km),  and also the speed model of atmosphere is made.